ANALISIS NILAI TUKAR DAN SUKU BUNGA TERHADAP INFLASI DIKOTA BATAM - Haposan Banjarnahor; Risca Azmania (Prosiding, 2026)
The global economy is currently heading toward a crisis due to the war between the United States alliance and Iran, which has triggered an energy crisis as supply through the Strait of Hormuz is disrupted. This has driven world oil prices up to $100 per barrel, increasing inflation in Batam by an estimated 1.8% – 2.2%. This study aims to analyze the effect of the Rupiah exchange rate against foreign currencies (USD), where the Rupiah is currently moving in the range of Rp17,387 – Rp17,405, and the benchmark interest rate (BI‑Rate), which Bank Indonesia has maintained at 4.75% for the April 2026 period. Given Batam’s position as a free‑trade zone that is highly dependent on imports and foreign exchange flows, national macroeconomic fluctuations often have a faster impact in this region. The method used is multiple linear regression with time‑series data sourced from the Central Statistics Agency (BPS) of Batam and Bank Indonesia. The results show that partially, the exchange rate has a positive and significant effect on inflation, where Rupiah depreciation drives up the prices of imported goods (cost‑push inflation). Meanwhile, the interest rate has a negative and significant relationship with inflation in the short term, but its effect is weaker compared to the exchange rate. Simultaneously, both variables contribute 78.4% to the movement of inflation in Batam City. In conclusion, exchange rate stabilization policies are more effective than a single interest rate policy in controlling inflation in this trade‑ and export‑import‑based city. Keywords: Exchange Rate, Interest Rate, Inflation